Federal Finance in Theory and Practice : With special reference to Switzerland - Dafflon, Bernard (Bern ; Stuttgart : Paul Haupt, 1977)
This book provides a critical evaluation of contemporary theories of fiscal federalism from the standpoint of their relevance for practical policy. It explains the restrictive value judgments upon which they rest and the unrealistic economic efficient assumptions upon which their policy prescriptions depend.
Bibliography: p. 225-229.
osc 29/6/17
Loans
Keywords: Finance, Public; Intergovernmental fiscal relations; Intergovernmental fiscal relations